Antibacterial Activity and Characterization of Chitosan Nanoparticles Prepared from Hijau Lumut Banana (Musa paradisiaca L.) Peel Ethyl Acetate Extract - Wiwik Susanah Rita; Ni Kadek Linda Erika Yanti; I. Made Dira Swantara (Nano Biomedicine and Engineering, 2023)
Peels of Hijau lumut banana (HLB) (Musa paradisiaca L.) are a form of organic waste that has not been widely utilized. This study was conducted to determine the antibacterial activity of ethyl acetate extract of HLB peels and that of their nanoparticles at various concentrations of chitosan against Staphylococcus aureus and Escherichia coli. It was also aimed to characterize the most active nanoparticles. Extraction of HLB peels was carried out by maceration and partitioning methods. Ionic gelation was applied to synthesize nanoparticles using chitosan crosslinked with sodium tripolyphosphate (NaTPP). Antibacterial activity assay was carried out by the agar diffusion well method. The nanoparticles were characterized by the following analyses: determination of their size distribution and zeta potential by a particle size analyzer, and of their morphology by scanning electron microscopy and transmission electron microscopy, phytochemical screening to determine secondary metabolite contents, determination of retention factor values and staining patterns by thin-layer chromatography, ultraviolet–visible (UV–Vis) spectrophotometry to confirm nanoparticle formation, and determination of the characteristics of their functional groups by Fourier transform infrared spectrophotometry. The antibacterial activity assay showed that the nanoparticles exhibited a stronger antibacterial activity than the ethyl acetate extract, with chitosan at a concentration of 1% being associated with the highest activity. In terms of their morphology, the nanoparticles were amorphous (non-uniform), while they absorbed UV–Vis at 385 nm and had the following functional groups: —OH, —NH, —CH, and P—O. This study revealed that these nanoparticles exert antibacterial effects and the secondary metabolites were encapsulated via crosslinking between chitosan and NaTPP.